Analisis Technology Acceptance Model (TAM) Terhadap Tingkat Penerimaan E-learning Pada Kalangan Mahasiswa (Studi Empiris Pada Universitas Internasional Batam dan UPBJJ-UT Batam) - Harris, Ibnu (Jurnal Terapan Manajemen dan Bisnis, 2017)
ICT adoption and diffusion studied in detail lately by researchers in the information systems area. It studied at two levels: the first is at the organizational level and the other is at the individual level. If the unit analysis is an individual, the emphasis is on the acceptance of technology (Dasgupta, Granger & Mcgarry, 2002).TAM is an intention-based model developed specifically for explaining and/or predicting user acceptance of computer technology (Hu, et.al., 1999). Technology acceptance defined as âan individualâs psychological state with regard to his or her voluntary or intended use of a particular technologyâ (Masrom, 2007). Therefore, in this study TAM is used to study the acceptance of the e-learning technology.The research presented here motivated and guided by two main questions. First, do students (learners or users) would like to accept e-learning or vice versa? Second, what are the factors that significant in explaining the usage towards e-learning?, that is, do the attitudinal beliefs such as perceived ease of use and perceived usefulness has relationship towards the e-learning adoption? In other words, this study examined TAM and the external factors in an academic setting, testing the factors affecting studentsâ acceptance of e-learning technology.